Hygrothermal aging behavior of regenerated cellulose fiber-reinforced polyamide 5.10 composites - Celia Katharina Falkenreck; Jan-Christoph Zarges; Hans-Peter Heim (Polymer Testing)
The effects of hygrothermal aging on the crystallinity, molecular structure and viscosity as well as on the quasi-static behavior of regenerated cellulose fiber-reinforced (RCF) bio-based polyamide (PA) 5.10 were examined in this study. Composites with 20 wt% RCF were produced on a twin-screw extruder and non- and RCF-reinforced specimens were manufactured on an injection molding machine. Specimens were aged in a climate chamber under conditions of four temperatures (23 °C, 50 °C, 70 °C, 90 °C) and five relative humidities (10 %rH, 25 %rH, 50 %rH, 75 %rH, 90 %rH). Once hygrothermal aging was carried out, tensile tests, μCT images as well as DSC, FTIR, GPC, moisture and rheology measurements have been performed on aged specimens and compared with results obtained from non-aged specimens. In addition, the influences of temperature and relative humidity were investigated using a 2nd-degree polynomial regression. Strong hydrolytic and thermo-oxidative influences were detected in combination with elevated temperatures, which accelerate the degradation of the PA5.10. Furthermore, a strong association between aging and moisture content was demonstrated, which corresponds with the resulting mechanical properties. An influence of the inhomogeneous saturation of the PA5.10 on the molecular chain splitting processes could also be shown. The RCF have a positive effect on the durability of PA5.10. However, fiber-matrix-debonding due to swelling processes of the RCF, which have been detected in μCT images, reduce the tensile strength and young's modulus significantly.